Konstruktion Von Sprache und Sprachwissen : Eine Empirische Studie Zur Schriftsprachaneignung Sprachstarker und Sprachschwacher Kinder. - Schaller, Pascale (Berlin/Boston : Walter de Gruyter GmbH, 2018)
The German Linguistic Studies Series is a comprehensive and outstanding forum in its field. It has borne the name of its subject in its title since the foundation of the series in the eighth decade of the last century. The series is comprehensive in the broad spectrum of topics covered (language levels, varieties, communication forms, epochs) in the range of research perspectives (theoretical and empirical studies, fundamental research and applications, interdisciplinarity with psychology, the social sciences etc.) and methodologies (the sole criterion is quality), in the rhythm of research (trends are perceived and also set, achievements are secured) and in the forms of presentation (monographs, textbooks, collected volumes, dictionaries). Professorial theses, outstanding doctoral theses, pioneering research findings from wider contexts, but also the surprising ‛stroke of genius' set the standards for inclusion in the series.
Intro -- Vorwort -- Inhalt -- 1. Einleitung -- 2. Thematik und Übersicht -- I. Forschungstheoretischer Hintergrund -- 3. Soziogenese und Ontogenese der Schriftsprache -- 4. Schreiben als Prozess -- 5. Grundlagen und Formen der Sprachbetrachtung -- 6. Sprachliche Konstruktionen zwischen Produkt, Prozess und Sprachwissen -- II. Konzeptualisierung der Untersuchung -- 7. Herleitung der Forschungsfragen -- 8. Operationalisierung der Variablen -- 9. Erhebungsinstrumente und Methode -- 10. Korpus und Beschreibung der Stichprobe -- III. Untersuchungsbericht -- 11. Auswertungen entlang der Hauptfragestellungen -- 12. Zusammenfassung und Diskussion -- 13. Fazit und Ausblick -- IV. Anhang -- 14. Bibliographie -- 15. Abbildungs- und Tabellenverzeichnis -- 16. Erhebungsmaterial -- 17. Exemplarische Auszüge aus dem Datenkorpus -- Register.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books